2002
DOI: 10.1128/aem.68.7.3467-3477.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Diversity within Species of Purple Nonsulfur Bacteria Isolated from Aquatic Sediments

Abstract: To assess the extent of genotypic and phenotypic diversity within species of purple nonsulfur bacteria found in aquatic sediments, a total of 128 strains were directly isolated from agar plates that had been inoculated with sediment samples from Haren and De Biesbosch in The Netherlands. All isolates were initially characterized by BOX-PCR genomic DNA fingerprinting, and 60 distinct genotypes were identified. Analyses of 16S rRNA gene sequences of representatives of each genotype showed that five and eight dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 50 publications
2
49
0
1
Order By: Relevance
“…This procedure impedes linkage of varying geographical distance to varying ecology. Interestingly, other studies have observed indications of natural selection (16)(17)(18); however, the results were not linked either to ecology (17) or to the effect of geographic distance (18).…”
mentioning
confidence: 69%
“…This procedure impedes linkage of varying geographical distance to varying ecology. Interestingly, other studies have observed indications of natural selection (16)(17)(18); however, the results were not linked either to ecology (17) or to the effect of geographic distance (18).…”
mentioning
confidence: 69%
“…This is the largest number of RND pumps observed in any bacterium to date and may explain the high intrinsic resistance of R. palustris to antibiotics. R. palustris has been isolated in high numbers from polluted environments 36 . Heavy metal efflux transporters should allow R. palustris to live in a variety of environments and still acquire the necessary nutrients while resisting heavy metal toxicity.…”
Section: Transportmentioning
confidence: 99%
“…Members of the genus Rhodopseudomonas are characterized by having budding cell morphology, lamellar photosynthetic membranes, bacteriochlorophyll a and carotenoids of the sprilloxanthin series as the photopigments, and ubiquinone-10 as the major quinone. They are physiologically versatile and inhabit a wide variety of natural environments such as soil, freshwater, hot springs, and wastewater treatment systems (Hiraishi and Kitamura, 1984;Hisada et al, 2007;Oda et al, 2002Oda et al, , 2003aOkubo et al, 2005). In natural habitats, members of Rhodopseudomonas grow well in polluted waters and may have a higher affi nity to organic substrates compared to other PPNS bacteria such as those of the genus Rhodobacter (Okubo and Hiraishi, 2007;Okubo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%